Cause-Specific Mortality among HIV-Infected Persons in One Medical Center, Tehran, Iran - Arab-Mazar, Zahra; Hadavand, Fahimeh; Tabarsi, Payam; Abbasi, Fatemeh (Novelty in Biomedicine, 2019)
Background: Human immunodeficiency virus (HIV) is one of the major infectious agents, which has important role in the public health challenges, which have affected the world’s economic and social situation recent decades. During the last decades, millions of people died due to HIV infection worldwide. However, data remain limited on the causes of death among HIV-infected in Iranian population. The aim of the present study was to assess the cause specific death among HIV positive inpatient persons in Iran. Materials and Methods: This surveillance was conducted on inpatient HIV positive admissions at Masih Daneshvari Hospital, Tehran, Iran during October 2016 and April 2017.All patient’s data were collected via abstraction form, which were ascertained, from medical records and from written logbooks that were kept by the nursing staff on the ward. The data of each admission was recorded from the medical reports at the time of admission and upon discharge. All laboratory data were collected and recorded separately. Results: Fifty persons were diagnosed as HIV-infected patients, of which 58% of them were classified as AIDS patients. Our findings indicated that the cause of hospitalization were pulmonary 54%, neurological 20%, gastrointestinal 16%, and dermal 10% complications. Overall, 21 patients (42%) were diagnosed with pulmonary tuberculosis, of which one patient died from tuberculosis complications. Four patients died during the study period. Conclusion: In conclusion, early treatment and/or early use of ART can be improved outcomes. Therefore, early HIV testing and early ART use play important role in mortality reduction among eligible persons.